Lateral habenula astroglia modulate the potentiating antidepressant-like effects of bright light stimulation in intractable depression - Delcourte, Sarah; Bouloufa, Amel; Rovera, Renaud; Brunet, Elie; Le, Hiep D.; Williams, April E.; Panda, Satchidananda; Azmani, Rihab; Raineteau, Olivier; Dkhissi-Benyahya, Ouria; Haddjeri, Nasser (Frontiers in Pharmacology, 2025)
BackgroundBeside image vision, light plays a pivotal role in regulating diverse non-visual functions, including affective behaviors. Recently, bright light stimulation (BLS) was revealed to be beneficial for treating non-seasonal depression, although its mechanism of action is not fully understood.MethodsWe developed a novel mouse model of refractory depression, induced through social isolation and chronic despair during the active (dark) phase of the animal, and we have tested if antidepressant treatments, including BLS, could protect against anxio-depressive-like behavior.ResultsWe report that anxiety- and depressive-like behaviors are resistant to BLS as well as to both conventional and new antidepressants, including ketamine. Remarkably, we unveil that BLS potentiates the effect of antidepressants, and this beneficial effect is mediated via rod retinal photoreceptors. Furthermore, we demonstrate that both chemogenetic activation of lateral habenula (LHb) astroglia and serotonin (5-HT) depletion prevent the potentiating effect of BLS on chronic despair.ConclusionThese results reveal, for the first time, that BLS enhances the efficacy of antidepressants through an unexpectedly circuit involving rods, LHb astroglia and 5-HT.